1998
DOI: 10.1097/00003072-199809000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Tc-99m MIBI Thoracic SPECT for the Detection of Intrathoracic Tumor Masses

Abstract: Thirty-one men (age range, 46-76 years; mean age, 64.8 years) with intrathoracic masses suggesting possible malignancy on the basis of chest radiography or CT underwent preoperative Tc-99m MIBI SPECT examinations. Diagnosis was confirmed on pathologic examinations of samples obtained either at thoracotomy, esophagectomy, or by biopsy. Twenty-five patients had primary lung cancer, including squamous cell carcinoma, large cell carcinoma, adenocarcinoma, and small cell carcinoma. Two patients had lymphomas with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Its uptake mechanism involves passive diffusion across plasma and mitochondrial membranes. At equilibrium, strong negative transmembrane potentials propagate a concentration of the agent within the inner matrix of mitochondria [13]. Recently, 99m Tc-MIBI has been used as a tumor-imaging agent to detect various kind of tumors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its uptake mechanism involves passive diffusion across plasma and mitochondrial membranes. At equilibrium, strong negative transmembrane potentials propagate a concentration of the agent within the inner matrix of mitochondria [13]. Recently, 99m Tc-MIBI has been used as a tumor-imaging agent to detect various kind of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports describe the accumulation of 99m Tc-MIBI in breast, thyroid, bone, brain, and lung cancer [10], while only sporadic cases described 99m Tc-MIBI uptake in patients with anterior mediastinal mass. Shih et al [13] valuated the role of 99m Tc-MIBI uptake as an indicator of malignancy in 31 patients with intrathoracic masses; 2/31 patients were affected by anterior mediastinal lymphoma and both showed an increased uptake of tracer on SPECT images. The role of 99m Tc-MIBI-SPECT in identifying lymphoma has been also confirmed by Maura et al [15], who reported a diagnostic accuracy of 85% for the detection of this lesion in 31 patients, of whom five patients was affected by lymphoma localized within the anterior mediastinum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiopharmaceuticals containing either technetium-99m ( 99m Tc) or thallium-201 ( 201 Tl) are more affordable than FDG since they can be produced on site and do not need a cyclotron facility. These markers accumulate in lung carcinoma and, therefore, pulmonary lesions can be evaluated with widely available gamma cameras [7][8][9][10][11]. Methoxy isobutyl isonitrile (MIBI) is taken up primarily by mitochondria and studies have shown favourable characteristics in the evaluation of SPN, albeit only in settings with low incidence of benign lesions [10][11][12].…”
mentioning
confidence: 99%
“…These markers accumulate in lung carcinoma and, therefore, pulmonary lesions can be evaluated with widely available gamma cameras [7][8][9][10][11]. Methoxy isobutyl isonitrile (MIBI) is taken up primarily by mitochondria and studies have shown favourable characteristics in the evaluation of SPN, albeit only in settings with low incidence of benign lesions [10][11][12]. The present study was conducted to evaluate MIBI for the differentiation of benign from malignant pulmonary nodules in a population with high prevalence of TB and no access to a PET facility.…”
mentioning
confidence: 99%